Convergence to Efficiency in a Simple Market with Incomplete Information - Rustichini, Aldo; Satterthwaite, Mark A.; Williams, Steven R. (Econometrica, 1994)
A model of trade with m buyers and m sellers is considered in which price is set to equate revealed demand and supply. In a Bayesian Nash equilibrium, each trader acts not as a price-taker, but instead misrepresents his true demand/supply to influence price in his favor. This causes inefficiency. We show that in any equilibrium the amount by which a trader misreports is O(1/m) and the corresponding inefficiency is O(1/m2). The indeterminacy and the inefficiency that is caused by the traders' bargaining behavior in small markets thus rapidly vanishes as the market increases in size.